Developing cat‐friendly clinics. Issue 4 (2nd April 2013) - Sparkes, Andrew
Abstract : With data showing that there has been a marked growth in cat ownership, cats have never had a more important role in clinical practice. Andrew Sparkes discusses how to tap into this demographic by developing 'cat‐friendly' clinics.